Rationally assembled nano-microarchitecture of MoS2 nanoflower tightly anchored on polypyrrole microtube towards constructing fire-safe EP composite. Issue 12 (15th June 2023) - Huang, Yajun; Zhao, Xiaolong; Fan, Minghao; He, Song; Wang, Junling
Abstract: As for organic flame retardants, the high dosages (up to 20 wt%) are usually required to achieve favorable flame retardancy, which often causes serious aggregation in epoxy resin (EP). Thus, the applications of flame retarded EP composites are restricted by the jeopardized mechanical property. Therefore, a nano-microarchitecture of MoS2 nanoflowers in-situ grown on polypyrrole microtube (P-Mo) is rationally constructed as flame retardant for EP. The peak heat release rate and total heat release are significantly reduced by 47.4% and 22.2%, when adding 3.0 wt% P-Mo, demonstrating the hindered heat release. Besides, the peak smoke production rate and peak CO yield show reductions of 46.8% and 62.9% separately, which proves the hindered toxicants emission. Thermogravimetric analysis/infrared spectrometry results also show the attenuated releases of toxic CO and NO. These results jointly demonstrate that using P-Mo can efficiently suppress the fire hazard of EP, ascribed to the physical barrier, chemical catalyzing and charring promotion actions. Surprisingly, the storage modulus value is enhanced by 20.9%, when only using 1.0 wt% P-Mo. Graphical abstract: Image 1 Highlights: Nano-microarchitecture of MoS2 nanoflower grown on polypyrrole microtube is designed. Marked inhibitions on heat and toxicants releases are discerned by adding P-Mo. The usage of P-Mo incurs the producing of compact char with high graphitized degree. Obviously promoted mechanical performance is also found after loading P-Mo.